2020
DOI: 10.1038/s41598-020-76713-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drought associated with high temperatures on Coffea canephora plantations: a case study in Espírito Santo State, Brazil

Abstract: Droughts are major natural disasters that affect many parts of the world all years and recently affected one of the major conilon coffee-producing regions of the world in state of Espírito Santo, which caused a huge crisis in the sector. Therefore, the objective of this study was to conduct an analysis with technical-scientific basis of the real impact of drought associated with high temperatures and irradiances on the conilon coffee (Coffea canephora Pierre ex Froehner) plantations located in the north, north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 94 publications
1
26
0
2
Order By: Relevance
“…Ultimately, the primary response beyond ABA levels will be the stomatal closure in coffee leaves, regulating ion transport in guard cells and decreasing drought severity in coffee genotypes as reported in other species [96][97][98] Climate changes are expected to include an increased frequency of water scarcity events, including the intensity of severity and duration, posing a growing threat to coffee's global supply chain. Agroforestry systems can be useful to mitigate some of these harsh effects, reducing the risk of coffee production losses and contributing to the sustainability of crops [18,31]. However, to maintain the global supply of coffee, it is also important to promote the screening and development of tolerant varieties to face the increasingly expected impacts of droughts.…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the primary response beyond ABA levels will be the stomatal closure in coffee leaves, regulating ion transport in guard cells and decreasing drought severity in coffee genotypes as reported in other species [96][97][98] Climate changes are expected to include an increased frequency of water scarcity events, including the intensity of severity and duration, posing a growing threat to coffee's global supply chain. Agroforestry systems can be useful to mitigate some of these harsh effects, reducing the risk of coffee production losses and contributing to the sustainability of crops [18,31]. However, to maintain the global supply of coffee, it is also important to promote the screening and development of tolerant varieties to face the increasingly expected impacts of droughts.…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
“…Currently, there is evidence that C. canephora has some tolerance to drought through enrichment of secondary compound metabolic genes, namely antioxidant genes, which play an essential role in coffee drought response [29]. Recent studies underline that at least some genotypes of C. canephora could be far more sensitive to thermal stress than previously thought [30,31]. Other genotypes of C. arabica and C. canephora were found to have the ability to endure harsh temperatures [23,24] and water deficit [25] to a greater extent than usually assumed.…”
Section: Introductionmentioning
confidence: 99%
“…The quite low levels of genetic variation found in C. arabica when compared to its diploid progenitors are a concern in the context of environmental changes regarding the sustainability of this crop [20]. The predicted increase in global temperature could be catastrophic to C. arabica yields and quality, since some works consider this species more sensitive to elevated temperatures than C. canephora [15], with impacts being already felt on field plantations [21,22]. In fact, classical studies suggested that coffee photosynthesis would be particularly sensitive to temperatures above 20-25 • C (e.g., [23][24][25]).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of climate change on microbial diversity and the resilience of toxigenic fungi through culture-independent technology has yet to be explored in the coffee crop. Drought is the main environmental restriction affecting coffee growth and production [ 79 ], not only for arabica coffee but also for robusta, which until recently was considered resistant to temperature increases, having been recently demystified by research conducted in Southeast Asia [ 80 ]. Some studies provided evidence that potential mycotoxigenic fungi may not be affected by the CO 2 treatments [ 81 ], nonetheless, these studies need to be better designed in order to include other climatic factors linked to the natural microbiome associated with coffee production/productivity [ 82 ].…”
Section: Post-harvest Microbial Ecology Of Coffee Beansmentioning
confidence: 99%
“…Thus, it is still mandatory to design indirect means of assessing the vulnerability of coffee microbiota to temperature change in the field allied to stress and other climate factors, such as water and CO 2 , to verify how these climatic factors influence the population fluctuation of microorganisms and microbial succession directly associated with the production of coffee beans. This information is still necessary for decision-making related to the sustainability of the coffee sector, since its production is considered the main agricultural product in some Brazilian states and may be jeopardized by climate change [ 79 ].…”
Section: Post-harvest Microbial Ecology Of Coffee Beansmentioning
confidence: 99%